Management Interventions to Reduce Incidence of Diarrhoea in Piglets during Pre Weaning Period (Indian Journal of Animal Production and Management, 2024)
A study was carried out at an organized pig  farm in Kalyani, West Bengal, to assess  effectiveness of management practices like teat  dipping and floor mopping on reduction of bacterial  load and diarrhoeal incidence during pre-weaning  period in piglets. Twenty lactating sows of  Ghoongroo breed along with their newborn piglets  (146 nos.) during pre-weaning period were studied.  In group 1 (control) floor of each farrowing pen was  washed with normal water. In group 2, additionally  teats of each sow were treated with 10% povidone  iodine dip. In group 3 floor of each farrowing pen  was washed with normal water followed by mopping  with 0.25% potassium permanganate. In group 4  both sow teat dipping and sty floor mopping with  disinfectant was done. It was observed that the  average bacterial load during the total pre-weaning  period of 8 weeks was 48.4x103± 5.3 x103 cfu/cm2 in control group, whereas the average bacterial load  was 34.0 x103±1.2X103 and 7.18 x102±0.10 x102 cfu/cm2 before and after teat dip application in group  2, and 32.5 x103±1.3 x103 cfu/cm2 and 6.98  x102±0.11 x102 cfu/cm2 in group 4, respectively,  indicating positive impact of teat dipping as well as  disinfectant floor mopping in reducing the bacterial  loads of sow teats. Regular teat dipping and sty  floor mopping can improve the body growth of  piglets, by reducing the occurrence of piglet  diarrhoea. Thus, the chances of economic losses  in pig production unit can be reduced.
Keywords: piglets; pre-weaning diarrhoea; teat dipping; floor mopping